Do We Have to Prohibit the Use of Mobile Phones in Classrooms? - Mohammad, Heba; Fayyoumi, Ayham; AlShathry, Omar (International Journal of Interactive Mobile Technologies (iJIM), 2015)
People take their mobile phones everywhere they go. In Saudi Arabia, the mobile penetration is very high and students use their phones for different reasons in the classroom. The use of mobile devices in classroom triggers an alert of the impact it might have on students’ learning. This study investigates the association between the use of mobile phones during classroom and the learners’ performance and satisfaction. Results showed that students get distracted, and that this diversion of their attention is reflected in their academic success. However, this is not applicable for all. Some students received high scores even though they declared using mobile phones in classroom, which triggers a request for a deeper study.